Comparison of ultrasound, digital, and conventional radiography in differentiating periapical lesions: An in vivo study - Purnachandrarao Naik Nunsavathu; Ravi Kiran Alaparthi; Samatha Yelamanchili; Neha Vashisht; Ravindra Naik Gugulothu; Sri Krishna Koppula (Wolters Kluwer Medknow Publications, 2015)
Aims and Objectives: To evaluate in vivo the efficacy of ultrasound, digital and conventional radiography in identifying periapical lesions. To compare the results of the above imaging modalities with histopathology, which is considered to be the gold standard for diagnosis. Materials and Methods: Thirty patients aged between 15 and 45 years with periapical lesions associated with maxillary or mandibular anterior teeth indicated for endodontic surgery or extraction were selected for the study. Pre-operatively, conventional, digital periapical radiography and ultrasonography were done and interpreted. Endodontic surgery or extraction was performed including curettage of apical tissue to enable histopathological investigation, which provided the gold standard diagnosis. All measurements and findings were compared and statistically analyzed. Results: In conventional and digital radiography, the periapical lesions were readily identified but observers were unable to differentiate granuloma from cyst using these modalities only. But ultrasonography was able to give the true nature of the periapical pathology. All the cases diagnosed by ultrasound were confirmed with histopathology, and maximal number of cases diagnosed by ultrasound correlated with the histopathological diagnosis. Conclusion: The present study confirms that ultrasound is a promising and reliable imaging technique for differentiating periapical lesions i.e., periapical cysts and granulomas. Based on the echo texture of their contents and the presence of vascularity using color Doppler, periapical cyst and granulomas can be readily identified. The present study is further applicable for the evaluation of periapical lesions of the posterior teeth and evaluation of other jaw lesions.